Social and Cultural Drivers Affecting The Uptake Of Maternal and Newborn Health Care Services Among Women in Their Reproductive Age in The East Mamprusi Municipality - Yussif, Adam Bawa; Mahama, Smith Wayo; Abudu, Jacob Ibrahim (Asian Journal of Health Research, 2025)
Introduction: Socio-economic and cultural factors affect the use of basic maternal and newborn health care services among women in their reproductive age in Ghana. Yet, little is known about women’s choice of such preferences. This study was conducted to assess social and cultural factors that affect the uptake of maternal and newborn health care services among women in their reproductive age in the East Mamprusi municipality of Ghana. Material and Methods: The study employed a descriptive cross-sectional study design using simple random sampling technique to sample the respondents at the study setting. Structured questionnaire of a question about knowledge, cultural factors, and social factors were used to collect the data. The collected data was filled on cleared for completeness and analysed using Statistical Package for Social Science Windows version 25.0 and Microsoft Word Excel 2016. Results: 81.5% mentioned that husband determined when ANC should be initiated. It was also revealed that, pregnant women preferred to be attended to by TBAs as compared to nurses. From the results, 89% of the respondents considered distance to access maternal and newborn care services as a social factor affecting maternal and newborn care. From the results, respondents who were staying more than 2 km away from a health centre were 2.26 times more likely to be knowledgeable on social factors that affects maternal and newborn health care services as compared to those who were staying less than 2 km away from a health centre [COR = 2.26 (95% CI 2.11, 24.88); p = 0.152]. Conclusion: Cultural and social factors affect women use of maternal and newborn health care.